The Influence of Match Status on Ball Possession in High Performance Women’s Football - Maneiro, Rubén; Losada, José L.; Casal, Claudio A.; Ardá, Antonio (Frontiers in Psychology, 2020)
Women's soccer is increasingly demanding performance and results to soccer players. It is a sport in expansion, reaching high shares of sports records and support from different football clubs. The world of research should not remain on the sidelines and should contribute, from a scientific perspective, to the development of this sport. Starting from a new methodological perspective, the mixed methods, the objective of this work has been to acknowledge the match status behaviour and how the different variables considered in the study can modulate the match status variable during games. For this, the most recent high level championship, the FIFA Women's World Cup 2015, has been analyzed, where the most representative and highest quality players and teams have gathered. Specifically, the 52 games played have been collected, and the 3740 ball possessions executed by teams have been analyzed. Teams have been divided into successful and unsuccessful, to know which variables modify match status according to whether teams have been winning or losing. For this, three types of analysis have been carried out: a univariate analysis for both groups with the categorical and continuous variables selected; a bivariate analysis, using chi-square tests and Fischer's exact test, where the aim was to study the relationship between the variables described; and finally, a multivariable technique such as decision trees was incorporated. This has allowed us to propose two different success models for each group considered. Results have allowed to corroborate significant differences between successful and unsuccessful teams regarding the match status variable. In particular, the behaviors of unsuccessful teams are clearly ineffective and unproductive, not allowing them to achieve victory with the variables considered. Successful teams present tactical behaviors that allow them to achieve victory in most matches. It has also been shown that successful teams have a greater number of possessions than unsuccessful teams. The results of this study can help provide valuable tactical information to coaches, in order to increase their performance during matches.